The impact of displacement on the expression of depressive disorder and social functioning among the war refugeesI - Radanović-Grgurić, Ljiljana (Array, 2009)
Our research objective was to estimate the characteristics of major depressive disorder and social adaptation of women displaced during the war in Croatia in the early 1990s. All depressed patients manifested poor social adaptation. Displacement characteristics were: the length of time spent in exile, the place, and the circumstances of displacement regarding the members of the family accompanying the displaced women. These characteristics significantly influenced the expression of their major depressive disorder as well as social functioning. Displaced persons/refugees are at high risk of developing depressive disorder. Recognition of all risk factors and early diagnosis of depressive disorder followed by appropriate treatment could decrease the risk of chronic and complicated depression as well as the risk of poor social adaptation.